Diagnostic applications of simultaneously acquired dual-isotope single-photon emission CT scans. - Mathews, D; Walker, B S; Allen, B C; Batjer, H; Purdy, P D (American Journal of Neuroradiology, 1994)
PURPOSE To report the development and validation of a technique of dual tracer single-photon emission CT brain imaging using technetium-99m hexamethylpropyleneamine oxime and iodine-123 iodoamphetamine agents and the application of this technique in patients with a variety of diagnoses. METHODS Contamination between the two isotopes' energy windows was calculated by opening both energy windows while scanning a group of patients using a single isotope. To compare uniformity of I-123 down-scatter, Tc-99m studies were performed both before and after the administration of I-123 in five of 24 dual studies. The 24 patients studied with the dual-isotope technique were evaluated during acetazolamide testing, trial balloon occlusion, or embolization of an arteriovenous malformation. RESULTS In a dual acquisition, average count contamination of an I-123 study by Tc-99m was less than 1% of the total I-123 counts, and contamination of a Tc-99m study by I-123 was approximately 12% of the total Tc-99m counts. Tc-99m studies performed both before and after the administration of I-123 demonstrated that contaminating counts do not adversely affect scan interpretation. Dual-tracer scans were completed in all 24 patients, 10 of whom showed changes after intervention. CONCLUSIONS Dual-tracer single-photon emission CT brain scans of adequate diagnostic quality are possible using Tc-99m and I-123.